Numerical simulation of bending stress at variable loads in plastic gears - Moya Rodríguez, Jorge Laureano (2012)
The tests on test rigs to simulate the real contact conditions generated between the teeth of a gear, but are expensive and of limited utility for its accuracy depends on the condition of equipment and material. The objective of this research is to develop a procedure that simulates the bending stress in gear teeth plastic through numerical simulation method and the study of the main parameters that affect the performance of plastic gears such as torque, power and efforts of these gears when in operation regime, comparing with the molten steel. The results of this research meet the general and specific objectives of the study, which will help in improving the technology of Peruvian industry.